2011
DOI: 10.1002/ar.21243
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophic Serotonin Axons in Postmortem Brains from Young Autism Patients

Abstract: Autism causes neuropathological changes in varied anatomical loci. A coherent neural mechanism to explain the spectrum of autistic symptomatology has not been proposed because most anatomical researchers focus on point-to-point functional neural systems (e.g. auditory, social networks) rather than considering global chemical neural systems. Serotonergic neurons have a global innervation pattern. Their cell bodies are found in the midbrain but they project their axons throughout the neural axis beginning in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 104 publications
(97 reference statements)
3
17
0
Order By: Relevance
“…Axons in the superficial white matter below the orbitofrontal exhibited significantly thinner myelin sheaths when controlled for axon diameter despite similar numbers of oligodendrocytes (Zikopoulos and Barbas, 2010). Azmitia et al (2010, 2011) also found a significant excess of morphologically abnormal serotonin axons in principle ascending fiber bundles of the medialand lateral forebrain bundles as well as target areas in the temporal cortex, amygdala, and globus pallidus.…”
Section: Altered Cortical White Matter: Evidence From Dti and Postmormentioning
confidence: 89%
“…Axons in the superficial white matter below the orbitofrontal exhibited significantly thinner myelin sheaths when controlled for axon diameter despite similar numbers of oligodendrocytes (Zikopoulos and Barbas, 2010). Azmitia et al (2010, 2011) also found a significant excess of morphologically abnormal serotonin axons in principle ascending fiber bundles of the medialand lateral forebrain bundles as well as target areas in the temporal cortex, amygdala, and globus pallidus.…”
Section: Altered Cortical White Matter: Evidence From Dti and Postmormentioning
confidence: 89%
“…An increased number of dystrophic thick SERT-ir fibers has been noted in the amygdala, the hippocampus, and the cortex of autistic patients (Azmitia et al, 2011). Interestingly, rodents exposed neonatally to CTM showed an increased number of thick and rod-like SERT-ir fibers and/or fine and beaded SERT-ir fibers in the cortex and hippocampus (Maciag et al, 2006; Weaver et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The areas for analysis were photographed from coded slides to include layers II– V of the temporal and fusiform cortices, midbrain tegmentum, pontine fibers and cerebellar cortex. All pictures were stored by code for analysis using NIH ImageJ as previously described (see Akbari et al 1994; Azmitia et al 2011a, b). Stereological measures were made directly from the brain slides as previously described (Boldrini et al 2012).…”
Section: Methodsmentioning
confidence: 99%